1997
DOI: 10.1007/s003300050221
|View full text |Cite
|
Sign up to set email alerts
|

MRI of pancreatic tumors

Abstract: MRI employing current imaging techniques is able to detect various pancreatic tumors well, and is able to stage and characterize tumors accurately. This review article describes various current MR techniques emphasizing breath hold spoiled gradient echo (SGE) imaging, fat suppression, dynamic gadolinium administration and MR cholangiographic techniques. Pancreatic ductal adenocarcinomas are generally low signal intensity on T1-weighted and T2-weighted images and enhance poorly on immediate post gadolinium SGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 49 publications
(90 reference statements)
0
17
1
1
Order By: Relevance
“…These tumors exhibit low signal intensity on T1-and T2-weighted MR images, and show less enhancement than the parenchyma of the pancreas on gadolinium-enhanced GRE MR images [13]. Mangafodipir is an organ-specific MR contrast agent that accumulates predominantly in the liver and the parenchyma of the pancreas [14].…”
Section: Discussionmentioning
confidence: 99%
“…These tumors exhibit low signal intensity on T1-and T2-weighted MR images, and show less enhancement than the parenchyma of the pancreas on gadolinium-enhanced GRE MR images [13]. Mangafodipir is an organ-specific MR contrast agent that accumulates predominantly in the liver and the parenchyma of the pancreas [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fat-saturated T1-weighted images are useful in the detection of pancreatic tumors. On fat-saturated T1-weighted images, respiratory motion and chemical shift artifacts reduce and the contrast between tumor and normal parenchyma definitely increases [2,4,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous ultrasound (US), CT scan and MRI are wellestablished procedures used in the evaluation of pancreatic masses (9,10). CT is the most common imaging technique used in the detection and characterization of pancreatic tumors.…”
Section: Discussionmentioning
confidence: 99%